Masjid Jamik sebagai Jejak Sejarah Peninggalan Komunitas India Muslim di Kota Medan - Harahap, Nur Jannah; Siregar, Syahruddin; Purwaningtyas, Franindya (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article discusses the Jamik Mosque as a proof of the presence of Muslim Indians in the city of Medan. This study uses a qualitative research method with a descriptive approach that aims to find and describe the meaning of the shape of the mosque. The arrival of Indians to East Sumatra was initially recruited to become contract laborers in various tobacco plantations owned by Dutch businessmen. Then the 9th Sultan of Deli, Sultan Makmul al-Rashid, donated his land to the Indians as a place for them to live. The land given by the Sultan of Deli is currently known as Kampung Keling or Kampung Madras. On that land the Indian Muslim community established two mosques, namely: the Jamik Mosque and the Ghaudiyah Mosque. Jamik Mosque was built in 1887 AD, and is one of the oldest mosques in Medan City. In this article, this author examines the history of the Jamik Mosque and its transformation from a place of worship into a religious tourist spot.